TEORI DAN PROSES ISLAMISASI DI INDONESIA - Rosita Baiti; Abdur Razzaq (Wardah, 2014)
Various studies scientists and historians about the theories of the entry process and development of Islam in Indonesia, has always been a topic of interest also actual, to learn and explore, especially among Muslims, and especially the Muslims who are involved in the world of academia. This statement is closely related with the track record of the history, how the Indonesian nation in writing, through the relic inscriptions own civilization, culture and culture, even thought that is quite advanced, but can receive and adopt the culture, culture, beliefs, and foreign ideas (Islam) by peaceful means. This article will reveal scientifically how the process of Islamization in Indonesia based on historical facts.